PELATIHAN DAN PENDAMPINGAN PENGGUNAAN MEDIA PEMBELAJARAN MATEMATIKA PADA ORANG TUA SISWA SEKOLAH DASAR (SD) - Muhammad Jamaluddin; Mohammad Rifa’i; Roisatun Nisa’ (JPM PAMBUDI, 2018)
This program began with the problems that arose in the community, especially parents in terms of nurturing their kids. Field surveys conducted in three villages in the sub-district of Bungah Gresik, these were Abar-Abir, Pegundan, and Indrodelik that commonly the parents got difficulties in teaching math and also did not use the media in teaching their kids. They commonly invite a tutor to teach their kids. This case becomes the main problem in education. To overcome this problem, the team held training and mentoring the parents in using instructional media with demonstration and direct practice method. The learning media used in this program were mathematical ladder snakes, mathematical quadratic multiplication, mathematical puzzles, and math games. In training and mentoring the parents the team was assisted by students to explain the role of parents in using mathematics learning media. After the training and mentoring the team made a questionnaire to know the parents' perception and response in the use of mathematics learning media. The questionnaire results shown that the ideal percentage achieved 72.46%, it concluded that the use of mathematics learning media for teaching and mentoring the kids were good or satisfactory.